2013
DOI: 10.1002/cphc.201300215
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐Assisted Synthesis of HKUST‐1 and Functionalized HKUST‐1‐@H3PW12O40: Selective Adsorption of Heavy Metal Ions in Water Analyzed with Synchrotron Radiation

Abstract: A simple, rapid and efficient synthesis of the metal-organic framework (MOF) HKUST-1 [Cu3(1,3,5-benzene-tri-carboxilic-acid)2] by microwave irradiation is described, which afforded a homogeneous and highly selective material. The unusually short time to complete the synthesis by microwave irradiation is mainly attributable to rapid nucleation rather than to crystal growth rate. Using this method, HKUST-1-MW (MW=microwave) could be prepared within 20 min, whereas by hydrothermal synthesis, involving conventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(34 citation statements)
references
References 50 publications
0
33
0
Order By: Relevance
“…For example,p ristine MOF-5, am ember of the zinc-based MOF family,w as reported as efficient absorbents for the removal of copperi ons from aqueouss ystems. [140] To furtheri mprove the adsorption capacity and selectivity of heavy-metal ions, various functionalization methodsh ave been developed to modify pristine MOFs with desirable functional groups for the selective removal of heavy-metal ions from aqueous systems. More recently,Z hang et al reported that pristine zeolitic imidazolate framework( ZIF-8) could be directly used as apromising absorbent for the removal of Cu 2 + with high adsorption capacity and removal efficiency for Cu 2 + in aqueous systems.…”
Section: Mofs For Heavy-metal-ion Removal Applicationsmentioning
confidence: 99%
“…For example,p ristine MOF-5, am ember of the zinc-based MOF family,w as reported as efficient absorbents for the removal of copperi ons from aqueouss ystems. [140] To furtheri mprove the adsorption capacity and selectivity of heavy-metal ions, various functionalization methodsh ave been developed to modify pristine MOFs with desirable functional groups for the selective removal of heavy-metal ions from aqueous systems. More recently,Z hang et al reported that pristine zeolitic imidazolate framework( ZIF-8) could be directly used as apromising absorbent for the removal of Cu 2 + with high adsorption capacity and removal efficiency for Cu 2 + in aqueous systems.…”
Section: Mofs For Heavy-metal-ion Removal Applicationsmentioning
confidence: 99%
“…FTIR analysis of the synthesized MOF showed that its spectrum was similar to that of the samples prepared by Wei Li (Zou et al . ). The adsorption bands of (Arc–H) correspond to aromatic groups and the –OH bending vibrations of the water molecules observed at 3000–3500 cm −1 (Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 97%
“…where C i and C f are initial and final concentrations (mg/L), respectively, m is the amount of the adsorbent (g) and V is the volume of the solution (L). The effect of temperature on the adsorption capacity was evaluated at 298, 313, 328 and 343 K. The kinetic of adsorption process was studied between 5 and 120 min at 298 K. (Zou et al 2013). The adsorption bands of (Arc-H) correspond to aromatic groups and the -OH bending vibrations of the water molecules observed at 3000-3500 cm 21 (Supporting Information Fig.…”
Section: Adsorption Experimentsmentioning
confidence: 99%
“…In order to minimize the variables, optimize the yield, and control particle size, topology, and morphology, alternative synthesis methods have been investigated. These include in situ [12] and ex situ reaction methods [13,14], microwave assisted synthesis [15][16][17], electrochemical [18], mechanochemical [19], sonochemical [20], and ligand exchange [21,22].…”
Section: Introductionmentioning
confidence: 99%